2023
DOI: 10.1037/bul0000401
|View full text |Cite
|
Sign up to set email alerts
|

The development of subjective well-being across the life span: A meta-analytic review of longitudinal studies.

Susanne Buecker,
Maike Luhmann,
Peter Haehner
et al.

Abstract: How does subjective well-being (SWB) develop across the life span? Theories and previous empirical research suggest heterogeneous conclusions regarding this question. Therefore, in this meta-analysis, we synthesized the available longitudinal data on mean-level change in three SWB components: life satisfaction, positive affect, and negative affect. The analyses were based on 443 unique samples with a total of 460,902 participants. Our results showed that life satisfaction decreased from age 9 to 16 (d = −0.56)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 153 publications
0
7
0
Order By: Relevance
“…In a recent meta-analysis, it was reported that the trajectory of wellbeing depends on the measure of wellbeing, i.e. positive affect decreased across the lifespan, whereas life satisfaction was found to decrease during adolescence, increase in young and middle adulthood, and decreased again in late adulthood (Buecker et al, 2023). We used quality of life as measure, which is strongly related to life satisfaction (Bartels & Boomsma, 2009;Pavot, 2008), and showed a similar trajectory.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a recent meta-analysis, it was reported that the trajectory of wellbeing depends on the measure of wellbeing, i.e. positive affect decreased across the lifespan, whereas life satisfaction was found to decrease during adolescence, increase in young and middle adulthood, and decreased again in late adulthood (Buecker et al, 2023). We used quality of life as measure, which is strongly related to life satisfaction (Bartels & Boomsma, 2009;Pavot, 2008), and showed a similar trajectory.…”
Section: Discussionmentioning
confidence: 90%
“…Most of the research on the stability in wellbeing is performed in (white) samples from such high-income Western countries, i.e. Europe and the USA (Buecker et al, 2023). However, there are national differences in the average level of wellbeing experienced across the world (Helliwell et al, 2023) as well as cultural and societal differences in the experience of wellbeing (Joshanloo, 2014;Lomas et al, 2022;Tov & Diener, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To assess publication bias, we examined whether publication status predicted the effect size estimates (e.g., see Buecker et al, 2023). Furthermore, we conducted Funnel Plot Asymmetry Test (Egger et al, 1997) examining whether the standard error of the effect size estimates predicted the effect sizes.…”
Section: Meta-analyses (Not Preregistered)mentioning
confidence: 99%
“…For self-esteem, annual increases documented across the lifespan ranged between d = .00 and .088 in the meta-analysis of Orth et al (2018). For subjective well-being, average annual increases ranged between d = .002 and .007 for life satisfaction, d = .019 for positive affect, and d = .012 and .035 for negative affect (Buecker et al, 2023).…”
Section: Power Analysesmentioning
confidence: 99%
“…Due to the small sample size, we only focused on age and gender as matching criteria. These variables have previously been linked to differences in personality traits and characteristics (e.g.,Bleidorn et al, 2022;Buecker et al, 2023;Feingold, 1994;Kling et al, 1999;Schwaba et al, 2019) …”
mentioning
confidence: 99%